Individual Counseling Using Thought Stopping Techniques to Reduce Verbal Abuse Behavior in Students: Konseling Individu Teknik Thought Stopping dalam Mereduksi Perilaku Verbal Abuse Siswa - Luthfia Zahra; Fauziah Nasution (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Verbal abuse is a form of non-physical violence characterized by harsh, degrading, or mocking words that harm others emotionally, and it frequently occurs within school settings. Background (Specific): Addressing verbal abuse in students is crucial as it disrupts learning environments and affects peer relationships. Knowledge Gap: While Cognitive Behavioral Therapy (CBT) techniques have been applied in various behavioral issues, limited empirical evidence exists regarding their application in reducing students’ verbal abuse. Aim: This study investigates the use of individual counseling with the Thought Stopping technique to reduce verbal abuse among students. Results: Employing a pre-experimental one-group pretest-posttest design with purposive sampling, data were collected using a validated Likert-scale verbal aggression questionnaire and analyzed using the Wilcoxon signed ranks test in SPSS. Findings revealed a significant difference between pretest and posttest scores (p = 0.042, p < 0.05), indicating a measurable reduction in verbal abuse behavior after counseling. Novelty: This study demonstrates the application of a structured CBT-based intervention specifically tailored to address verbal aggression in school settings. Implications: The results highlight the potential of Thought Stopping in individual counseling as a practical strategy for educators and counselors to foster healthier communication patterns among students. Highlights: Individual counseling with Thought Stopping reduced students’ verbal abuse behavior. Wilcoxon test analysis showed a significant pretest–posttest difference (p=0.042). The study provides practical contributions for school counselors in behavior intervention. Keywords: Individual Counseling, Thought Stopping, Verbal Abuse, CBT, Students